A review of football injuries on third and fourth generation artificial turfs compared with natural turf - Williams, S.; Hume, P. A.; Kara, S. (Sports Medicine, 2011)
Football codes (rugby union, soccer, American football) train and play matches on natural and artificial turfs. A review of injuries on different turfs was needed to inform practitioners and sporting bodies on turf-related injury mechanisms and risk factors. Therefore, the aim of this review was to compare the incidence, nature and mechanisms of injuries sustained on newer generation artificial turfs and natural turfs. Electronic databases were searched using the keywords `artificial turf`,`natural turf`, `grass` and `inj*`. Delimitation of 120 articles sourced to those addressing injuries in football codes and those using third and fourth generation artificial turfs or natural turfs resulted in 11 experimental papers. These 11 papers provided 20 cohorts that could be assessed using magnitude-based inferences for injury incidence rate ratio calculations pertaining to differences between surfaces. Analysis showed that 16 of the 20 cohorts showed trivial effects for overall incidence rate ratios between surfaces. There was increased risk of ankle injury playing on artificial turf in eight cohorts, with incidence rate ratios from 0.7 to 5.2. Evidence concerning risk of knee injuries on the two surfaces was inconsistent, with incidence rate ratios from 0.4 to 2.8. Two cohorts showed beneficial inferences over the 90% likelihood value for effects of artificial surface on muscle injuries for soccer players; however, there were also two harmful, four unclear and five trivial inferences across the three football codes. Inferences relating to injury severity were inconsistent, with the exception that artificial turf was very likely to have harmful effects for minor injuries in rugby union training and severe injuries in young female soccer players. No clear differences between surfaces were evident in relation to training versus match injuries. Potential mechanisms for differing injury patterns on artificial turf compared with natural turf include increased peak torque and rotational stiffness properties of shoe-surface interfaces, decreased impact attenuation properties of surfaces, differing foot loading patterns and detrimental physiological responses. Changing between surfaces may be a precursor for injury in soccer. In conclusion, studies have provided strong evidence for comparable rates of injury between new generation artificial turfs and natural turfs. An exception is the likely increased risk of ankle injury on third and fourth generation artificial turfs. Therefore, ankle injury prevention strategies must be a priority for athletes who play on artificial turf regularly. Clarification of effects of artificial surfaces on muscle and knee injuries are required given inconsistencies in incidence rate ratios depending on the football code, athlete, gender or match versus training.